Sildenafil affects the human Kir2.1 and Kir2.2 channels at clinically relevant concentrations: Inhibition potentiated by low Ba2+ - Iijima, Akimasa; Švecová, Olga; Hošek, Jan; Kula, Roman; Bébarová, Markéta (Frontiers in Pharmacology, 2023)
Sildenafil (Viagra), the first approved and widely used oral drug for the treatment of erectile dysfunction, was occasionally associated with life-threatening ventricular arrhythmias in patients. Since inward rectifier potassium current (IK1) may considerably contribute to this arrhythmogenesis, we investigated the effect of sildenafil on the human Kir2.1 and Kir2.2, the prevailing subunits forming the ventricular IK1 channels. Experiments were performed by the whole-cell patch clamp technique at 37°C using Chinese hamster ovary cells transiently expressing the human Kir2.1 and Kir2.2 channels. Changes of both the inward and outward current components (at −110 and −50 mV, respectively) were tested to be able to consider the physiological relevance of the sildenafil effect (changes at −110 and −50 mV did not significantly differ, results at −50 mV are listed below). A significant Kir2.1 inhibition was observed at all applied sildenafil concentrations (16.1% ± 3.7%, 20.0% ± 2.6%, and 15.0% ± 3.0% at 0.1, 1, and 10 μM, respectively). The inhibitory effect of 0.1 μM sildenafil was potentiated by the presence of a low concentration of Ba2+ (0.1 μM) which induced only a slight Kir2.1 inhibition by 5.95% ± 0.75% alone (the combined effect was 35.5% ± 3.4%). The subtherapeutic and therapeutic sildenafil concentrations (0.1 and 1 μM) caused a dual effect on Kir2.2 channels whereas a significant Kir2.2 activation was observed at the supratherapeutic sildenafil concentration (10 μM: 34.1% ± 5.6%). All effects were fully reversible. This is the first study demonstrating that sildenafil at clinically relevant concentrations inhibits both the inward and outward current components of the main human ventricular IK1 subunit Kir2.1. This inhibitory effect was significantly potentiated by a low concentration of environmental contaminant Ba2+ in agreement with recently reported data on rat ventricular IK1 which additionally showed a significant repolarization delay. Considering the similar subunit composition of the human and rat ventricular IK1 channels, the observed effects might contribute to sildenafil-associated arrhythmogenesis in clinical practice.